Weave structures of polyester fabric affect the tensile strength and microplastic fiber emission during the laundry process - Onchanok Juntarasakul; Pongsiri Julapong; Palot Srichonphaisarn; Thidarat Meekoch; Dao Janjaroen; Carlito Baltazar Tabelin; Theerayut Phengsaart (Scientific Reports)
Abstract This study utilized grab and strip testing methods to examine the relationship between three weave structures—plain, twill, and satin—and their tensile strengths in both warp and weft directions. In addition, microplastic fiber (MPF) emissions from these three weave structures were quantified at different states of the laundry process using filtration and microscopy. The grab and strip tests revealed that twill- and satin-woven fabrics exhibited higher tensile strengths in the warp direction compared to the weft orientation. In contrast, the plain weave structure showed similar tensile strengths in both warp and weft directions. During laundry in the washing machine, MPF emissions in the first drainage were the highest regardless of the weave structure. Moreover, the satin weave pattern released the most MPFs among the three common weave structures at 5054 particles/L. This weave pattern also had the weakest tensile strength of 3.1 N/cm2 in the weft direction of the three weave structures evaluated. The results demonstrated a strong inverse correlation between higher tensile strengths in the weaker direction (warp or weft) and MPF emissions. Among the weave structures investigated, the twill pattern had the lowest MPF emission, followed by plain weave, with the satin-woven fabric emitting the highest levels.